Perception of organizational ethical behavior and individual ethical intention in Brazil - Lima, Marcelo Ribeiro de Mendonça (2020)
This study tested a model predicting that (i) ethical awareness and perception of organizational ethical behavior would be associated with individual ethical intention; and (ii) the perception of CSR and organizational identification would be associated, and in turn would have a positive effect on the perception of organizational ethical behavior. Through a survey, with longitudinal design in 3 waves, data were collected from 147 people in Brazil, as well as independent ratings of these professionals by 36 company coworkers who recruited them for the study. Results showed that, as predicted, higher levels of ethical awareness by individuals, as well as higher levels of perception of organizational ethical behavior, are both associated with higher levels of individual ethical intention. We also confirm that, as proposed, the perception of CSR has a positive effect on the perception of ethical organizational behavior, and is associated with organizational identification. Results did not confirm the expected effect of organizational identification on the perception of ethical organizational behavior. The study also discusses the implications of this research for theory and practice in Brazil, and suggests avenues for future research.